The Influence of Customer Loyalty through Customer Satisfaction with Islamic Religiosity as a Moderating Variable - Aminatur Rofiah; Titis Miranti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
With Islamic religiosity serving as a moderating factor, customer satisfaction with Bank Syariah Indonesia clients in Malang Raya is the study tool used to assess the impact of relationship and service quality on customer loyalty. a kind of quantitative study. 320 respondents from Malang Raya served as the sample size. Purposive and proportional random sampling are the sample methods used. Malang City, Malang Regency, and Batu City were all taken into account using proportional random sampling. Using SEM PLS, the data were examined. The study's conclusions show that although relationship quality has no appreciable effect on customer loyalty, customer happiness and service quality do have a significant impact. Customer happiness is significantly impacted by relationship and service quality. The mediation test indicates that customer satisfaction can influence customer loyalty via mediating the effects of service quality and relationship quality. Subsequent study findings, including the Islamic religiosity moderation test, demonstrated that the effects of customer happiness, relationship quality, and service quality on customer loyalty could not be balanced.